2016
DOI: 10.1175/jcli-d-16-0088.1
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainties in Projecting Future Changes in Atmospheric Rivers and Their Impacts on Heavy Precipitation over Europe

Abstract: This study investigates the North Atlantic atmospheric rivers (ARs) making landfall over western Europe in the present and future climate from the multimodel ensemble of phase 5 of the Coupled Model Intercomparison Project (CMIP5). Overall, CMIP5 captures the seasonal and spatial variations of historical landfalling AR days, with the large intermodel variability strongly correlated with the intermodel spread of historical near-surface westerly jet position. Under representative concentration pathway 8.5 (RCP8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
91
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 54 publications
10
91
0
Order By: Relevance
“…The relationship is somewhat consistent with the sensitivity experiments in Hagos et al [], although they found that the sensitivity of AR frequency to model resolution was notable only in the southeastern Pacific. Biases in landfalling AR frequencies in the west coasts of North America and Europe have been largely attributed to biases in the near‐surface subtropical jet locations [ Gao et al , , ]. Biases in AR zonal IVT are, in general, stronger than those in meridional IVT (Figures and ; note different scales between the two figures).…”
Section: Spatial Distributions Of Ar Frequency and Ivtmentioning
confidence: 56%
See 1 more Smart Citation
“…The relationship is somewhat consistent with the sensitivity experiments in Hagos et al [], although they found that the sensitivity of AR frequency to model resolution was notable only in the southeastern Pacific. Biases in landfalling AR frequencies in the west coasts of North America and Europe have been largely attributed to biases in the near‐surface subtropical jet locations [ Gao et al , , ]. Biases in AR zonal IVT are, in general, stronger than those in meridional IVT (Figures and ; note different scales between the two figures).…”
Section: Spatial Distributions Of Ar Frequency and Ivtmentioning
confidence: 56%
“…The importance of ARs in weather and climate has prompted increasing interests on the behavior of ARs in future climate [ Dettinger , ; Lavers et al , ; Payne and Magnusdottir , ; Warner et al , ; Radić et al , ; Gao et al , , ; Hagos et al , ; Ramos et al , ; Shields and Kiehl , , ]. A number of these studies involved, to different extents of comprehensiveness, the evaluation of model performance in simulating the behavior of ARs in the current climate, in order to establish credibility for the model projections.…”
Section: Introductionmentioning
confidence: 99%
“…While we maintain the >85th IVT PR threshold common to prior studies (e.g., Gao et al, ; Guan & Waliser, ; Nayak et al, ; Payne & Magnusdottir, ), we alter other criteria to account for potential differences in high‐latitude AR characteristics compared to typical midlatitude AR study regions. Because a few studies (Gorodetskaya et al, ; Guan & Waliser, ) have determined a relatively low IVT threshold is needed to reliably detect ARs in polar regions, we fix the minimum raw IVT value for potential AR identification at 150 kg m −1 s −1 rather than the value of 250 kg m −1 s −1 common in midlatitude AR studies (e.g., Rivera et al, ; Rutz et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Precipitation variability, manifesting in swing between extreme floods and droughts, poses significant risks to human lives, environment, society and properties, and challenges water management (e.g., Cayan et al, 1999;IPCC, 2012;Ralph et al, 2006;Warner et al, 2012). For example, an increase in extreme heavy rainfall under global warming has been reported widely in the literature (e.g., Gao et al, 2016;O'Gorman, 2015;Pendergrass & Gerber, 2016;Swain et al, 2018). For example, an increase in extreme heavy rainfall under global warming has been reported widely in the literature (e.g., Gao et al, 2016;O'Gorman, 2015;Pendergrass & Gerber, 2016;Swain et al, 2018).…”
Section: Introductionmentioning
confidence: 99%